2011
DOI: 10.1186/1297-9716-42-99
|View full text |Cite
|
Sign up to set email alerts
|

Higher whole-blood selenium is associated with improved immune responses in footrot-affected sheep

Abstract: We reported previously that sheep affected with footrot (FR) have lower whole-blood selenium (WB-Se) concentrations and that parenteral Se-supplementation in conjunction with routine control practices accelerates recovery from FR. The purpose of this follow-up study was to investigate the mechanisms by which Se facilitates recovery from FR. Sheep affected with FR (n = 38) were injected monthly for 15 months with either 5 mg Se (FR-Se) or saline (FR-Sal), whereas 19 healthy sheep received no treatment. Adaptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
5
12
0
Order By: Relevance
“…All sheep were bled at the end of the 15-month treatment period [7]. The experimental protocol was reviewed and approved by the Oregon State University Animal Care and Use Committee.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All sheep were bled at the end of the 15-month treatment period [7]. The experimental protocol was reviewed and approved by the Oregon State University Animal Care and Use Committee.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that sheep affected with FR have lower whole blood selenium (Se) concentrations and that Se supplementation in conjunction with routine control practices accelerates recovery from FR [7]. Foot rot is caused by infection with the bacterium Dichelobacter nodosus , an anaerobic bacterium, in association with other bacteria, particularly Fusobacterium necrophorum (reviewed in [7]). The role of the immune system in the etiology of FR is not well understood, and our goal is to understand the mechanism(s) by which Se may facilitate recovery from FR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strategies include parenteral antibiotic treatment, topical antibacterial sprays, trimming of horn hoof, vaccination, low stocking density, and genetic selection for sheep breeds less susceptible to FR [23], [25]. We previously documented in a small-scale study that WB-Se concentrations are lower in FR-affected compared with healthy sheep, and that supranutritional Se-supplementation (inorganic sodium selenite administered parenterally once monthly) hastens FR recovery [26].…”
Section: Introductionmentioning
confidence: 99%
“…Forage selenium levels in both the Idaho and Montana habitats averaged 8-10 times lower than what is recommended for domestic sheep forage of 0.25 and 0.30 ppm for whole blood levels to reach 0.2 ug/ml (Kincaid, 1998). Low blood Se levels are associated with immunosuppression (KiremidijianSchumacher & Stotzky, 1987, Hall et al, 2011). It has been speculated that bighorn sheep may have adapted to alpine environments and do not require as much Se as domestic animals (Samson et al, 1989).…”
Section: Forage and Habitat Evaluation: Domestic Sheep Nutritional Rementioning
confidence: 99%